Suitable dietary phospholipids improve lipid deposition, but excessive dietary phospholipids disorder lipid metabolism in juvenile leopard coral grouper (Plectropomus leopardus) - Xiangqin Lin; Yixiong Cao; Xuehan Wang; Xiaoxue Meng; Huajing Huang; Hang Zhou; Junming Deng; Beiping Tan (Aquaculture Reports, 2024)
Limited investigation has been available on the effects of dietary phospholipids in leopard coral grouper (Plectropomus leopardus), hindering its potential for aquaculture. This study was intended to investigate the impact of various levels (05 %) of dietary soy lecithin (SL) on juvenile P. leopardus over a 9-week feeding trial. Results indicated that dietary inclusion of 23 % SL enhanced the lipid content in liver, muscle, and whole-body. The fatty acid composition of muscle strongly reflected the dietary fatty acid profile. Furthermore, dietary inclusion of 3 % SL enhanced the activities of hepatic lipid synthesis enzymes [fatty acid synthase (FAS), glucose-6-phosphate dehydrogenase (G6PD)] and lipolytic enzymes [hormone-sensitive lipase (HSL), carnitine palmitoyltransferase-1 (CPT-1)]. Additionally, the inclusion of 23 % SL upregulated the relative expression of lipid synthesis-related genes [fas, sterol regulatory element binding transcription factor 1 (srebp1)] and lipid catabolism-related genes [hsl, cpt-1, and lipoprotein lipase (lpl)] in muscle. However, increasing dietary SL levels up to 45 % led to a reduction in muscle and whole-body lipid content, and an enhance in hepatic lipid content and hepatocyte vacuolization. Moreover, dietary inclusion of 5 % SL downregulated the relative expressions of hepatic lipid synthesis-related genes (g6pd and srebp1) and lipid catabolism-related genes (lpl and hsl). Overall, including 23 % SL in the diet improved lipid metabolism and thereby enhanced lipid deposition in juvenile P. leopardus, but excessive SL (45 %) disrupted lipid metabolism.